1997
DOI: 10.1590/s0101-81751997000200007
|View full text |Cite
|
Sign up to set email alerts
|

Haematological characteristics associated with parasitism in mullets, Mugil platanus Günther, from the estuarine region of Cananéia, São Paulo, Brazil

Abstract: ABSTRACT. This study involved 344 Mullets, Mugil plalanus Günther, 1880, captured in lhe estuarine region of Cananeia, São Paulo, Brazil (25°00'S, 47°55'W). The following data were recorded for each fish: total weight, total length, haemoglobin ratio (Hb), haematocrit (Ht), erythrocyte count (Er), differential leucocyte count (Iymphocytes, monocytes, neutrophils, basophils and "other cells") and haematometric indices; MCV, MCH, and MCHC. The sex and stage of gonadal maturity (undifferentiated, juvenile, restin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 15 publications
(13 reference statements)
5
16
0
3
Order By: Relevance
“…Mullet health in Cananéia was not affected by hirudinean parasitism. This was also verified by Ranzani-Paiva et al (1997) based on hematological parameters. The pathogenicity of monogenoideans varies according to species, infestation intensity, and attachment site.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Mullet health in Cananéia was not affected by hirudinean parasitism. This was also verified by Ranzani-Paiva et al (1997) based on hematological parameters. The pathogenicity of monogenoideans varies according to species, infestation intensity, and attachment site.…”
Section: Discussionsupporting
confidence: 62%
“…Specimens of mullet, Mugil platanus, from Cananéia, São Paulo State, Brazil, have been previously studied by Ranzani-Paiva & Ishikawa (1996) and Ranzani-Paiva et al (1997). Using the allometric condition factor (K) these authors did not detect any effect of parasitism on state of mullet health.…”
Section: Introductionmentioning
confidence: 99%
“…This is most likely due to the equilibrium between host and parasite. However, this equilibrium can be modified by any change in water quality and/or by rapid temperature fluctuations (PAIVA et al, 1997). The results of the present study were similar to those reported by Paiva et al (1997) for Mugil platanus parasitized by Monogenea.…”
Section: Discussionsupporting
confidence: 91%
“…However, this equilibrium can be modified by any change in water quality and/or by rapid temperature fluctuations (PAIVA et al, 1997). The results of the present study were similar to those reported by Paiva et al (1997) for Mugil platanus parasitized by Monogenea. On the other hand, Rio-Zaragoza et al (2010) did not find a hematological response in Lutjanus guttatus, Steindachner (1869) experimentally infected with Dactylogyridae, which showed an elevated number of erythrocytes and thrombocytes.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation